IMPROVEMENT OF CULTIVATION AND PROCESSING PRODUCTION PATCHOULI OIL AT THE VILLAGE AND VILLAGE FARMERS LEVEL SMALL AND MEDIUM SCALE AGROINDUSTRY IN VILLAGES PASE SENTAUSA KECAMATAN SIMPANG KEURAMAT NORTH ACEH DISTRICT - Muhammad Authar ND; Anwar Puteh; Barmawi; Nopri Yanto; Ade Bagus (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Patchouli oil is one of the country's foreign exchange earning commodities. This oil has strategic potential in the world market to be used as a fragrance binder in perfumes, cosmetics, the pharmaceutical industry, and other industries. Patchouli oil is produced through the distillation process of the patchouli plant (Pogostemon cablin Benth). However, the quality of patchouli oil produced in Indonesia is still relatively low because it is generally cultivated by traditional farmers or refiners whose quality control is very neglected. The purpose of this study was to determine the income and feasibility of Patchouli Oil production produced in the Patchouli Oil Processing Agro-industry at the Level of Village Farmers and Small and Medium Scale Agro-industry. This research was conducted in Pase Sentausa Village, Simpang Keuramat District, North Aceh Regency. Determining the location of this research was done purposively because in that area there are farmers who run patchouli farming and have a patchouli oil processing agro-industry. This research will describe the development of patchouli production. The results of the study, the net income of patchouli farmers in the patchouli oil industry business is Rp. 134,728,000. Patchouli oil industry business in producing patchouli oil with a value (R/C) > 1 of 3.55, patchouli oil refining agro-industry in Pase Sentausa Village, Simpang Keramat District, North Aceh Regency is feasible to be cultivated.